An Empirical Analysis on Cost Efficiency and Determinants of Commercial Banks in Hong Kong - NIE, YIMIN (2016)
This paper examines the cost efficiency of 35 commercial banks in Hong Kong over the period 2009 to 2014. By employing SFA method, the mean cost efficiency score of the sample commercial banks ranges from 88% to 97.66%. Meanwhile, the determinants of cost efficiency level are investigated, where Tobit regression model is utilized and the cost efficiency is adopted as dependent variable. Among the internal and external determinants, the GDP growth rate has a negative impact on Hong Kong commercial banks, while the net loan to total asset ratio is positively related to the cost efficiency level of the banks.